2019
DOI: 10.5114/aoms.2018.79682
|View full text |Cite
|
Sign up to set email alerts
|

Genes and metabolic pathway of sarcoidosis: identification of key players and risk modifiers

Abstract: IntroductionSarcoidosis is a rare multisystem granulomatous disease with unknown etiology. The interplay of vitamin D deficiency and genetic polymorphisms in genes coding for the proteins relevant for metabolism of vitamin D is an important, but unexplored area. The aim of this study was to investigate the association between single nucleotide polymorphisms (SNPs) in CYP2R1 (rs10741657), CYP27B1 (rs10877012), DBP (rs7041; rs4588), and VDR (rs2228570) genes and sarcoidosis, as well as the association between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
3
9
0
Order By: Relevance
“…Our study found that children with AA genotype of CYP27B1 gene had higher level of 25(OH) D compared to CC and CA genotypes. These findings are supported by other study where higher level of 25(OH) D was found for AA genotype and lower level for CC genotype in sarcoidosis patient 52 . GC gene encodes the vitamin-D binding protein (DBP) that is responsible for binding and transportation of vitamin D and its metabolites 56 .…”
Section: Discussionsupporting
confidence: 89%
“…Our study found that children with AA genotype of CYP27B1 gene had higher level of 25(OH) D compared to CC and CA genotypes. These findings are supported by other study where higher level of 25(OH) D was found for AA genotype and lower level for CC genotype in sarcoidosis patient 52 . GC gene encodes the vitamin-D binding protein (DBP) that is responsible for binding and transportation of vitamin D and its metabolites 56 .…”
Section: Discussionsupporting
confidence: 89%
“…The pathogenesis of SARC is related to the metabolism of vitamin D. The active form of vitamin D, 1,25-(OH)-2-D3, regulates immune response via cytokine expression, including IFN-γ and IL-2 [ 30 ]. The expression of vitamin D receptors in diseased BALT cells increases, and nodular granulomatous macrophages overproduce 1,25-dihydroxyvitamin D; hypercalcemia also manifests in these patients (10%) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding genetic determinants, numerous genome-wide association studies (GWAS) have identified multiple genetic modifiers of vitamin D serum levels and biological effects, including single-nucleotide polymorphisms (SNPs) in genes coding for key proteins involved in vitamin D metabolism, transport, and signaling, which could be considered in the clinical management with vitamin D. In particular, various polymorphisms in genes encoding 7-dehydrocholesterol reductase (DHCR7, which shunts vitamin D precursors toward cholesterol biosynthesis); cytochrome P450 vitamin D hydroxylases, including CYP2R1 (25-hydroxylase), CYP27B1 (1α-hydroxylase), and CYP24A1 (24-hydroxylase); vitamin D binding protein (VDBP, also known as GC globulin); and vitamin D receptor (VDR) were found to be statistically significantly associated with inter-individual variations in serum 25(OH)D and 1,25(OH)2D levels, either at baseline or after vitamin D supplementation [109,110], as well as with susceptibility to various human diseases [98,[110][111][112][113][114]. More specifically, distinct randomized controlled trials (RCTs) and systematic reviews/meta-analyses have shown that genetic variants in CYP2R1 (rs10766197, rs10741657, rs12794714, rs1562902, rs2060793), CYP24A1 (rs2209314, rs2762939, rs6013897), and VDBP (rs7041, rs4588) are either associated with baseline serum 25(OH)D levels or modify the efficacy of vitamin D supplementation in increasing such levels [109,110,[114][115][116].…”
Section: Determinants Of Vitamin D Status and Related Health Outcomesmentioning
confidence: 99%